PROBLEMATIKA NIKAH SIRRI DI INDONESIA - Siti Maryam Qurotul Aini; Inna Haqiyatar Rofi’ah (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2023)
The problems of sirri marriage in Indonesia can be described in terms of causative factors, law and legal consequences. Factors behind the occurrence of sirri marriages include obstacles to polygamy, pregnancy out of wedlock, age factors, economic factors and others. Although syar'i sirri marriage has fulfilled the pillars and conditions of marriage, due to the absence of marriage registration as mandated by the Marriage Law in Indonesia, sirri marriage does not have legal certainty and has an impact on the parties. The impact of sirri marriage is generally detrimental to women and children born in sirri marriage. Of course this must be anticipated by taking various steps, including the socialization of the importance of registering marriages. Thus the phenomenon of the rise of sirri marriages does not continue to be repeated and cause various problems.